Gender and Authorship in Annals of Surgery: A nineteen-year review including the pandemic - Jane W. Liang, PhD; Marcello Chang, MD, MCS; Sharon L. Stein, MD; Arghavan Salles, MD, PhD (Annals of Surgery Open)
Objective:. We examined article submission data from the Annals of Surgery to assess gender bias in publishing. Background:. Medicine has long been a male-dominated practice, particularly in surgical fields. A key criterion for promotion in academic medicine is the publication record. Thus, it is critical to understand the extent to which there are gendered disparities in access to publishing which may contribute to differences in career advancement, especially given the exacerbation of these disparities in the early part of the COVID-19 pandemic. Methods:. Working with Annals of Surgery submission data (2005–2023), we assigned author genders using genderize.io. Primary outcomes were final decision on the article (acceptance or rejection) and time to decision. Differences were examined between first-author gender, last-author gender, and first-author/last-author gender pairs using regression and chi-squared analyses. Results:. Men submit more articles than women. This gap widened until the number of submissions peaked in 2020, after which submissions from men appeared to decrease at a faster rate than those from women. Acceptance rates and time to decision have generally declined over time, but articles by women experienced, on average, higher acceptance rates and longer time to decision during recent years compared with those by men. Conclusions:. Our data from a single journal suggest that the widening gender gap in submissions that existed before the pandemic may be narrowing, and overall research productivity of academic surgeons may be declining. Further work is needed to examine the long-term productivity and career trajectories of academic surgeons by gender accounting for the ongoing pandemic.